2018
DOI: 10.1016/j.ijrobp.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase 2 Trial of C is/Carboplatin, nAb -Paclitaxel, and C e TUX imab ( CACTUX ) as First-Line Therapy for Recurrent/Metastatic Head and Neck Squamous Cell Carcinoma

Abstract: To quantify HPV16 copies in plasma circulating tumor DNA (ctDNA) from patients with favorable risk, HPV-associated oropharyngeal squamous cell carcinoma (OPSCC) during the receipt of deintensified chemoradiotherapy (CRT) on a prospective phase II clinical trial (NCT02281955). Materials/Methods: The major inclusion criteria were: 1) T0-T3, N0-N2c, M0, 2) HPV or p16 positive (tumor sample), and 3) minimal/moderate smoking history. De-intensified CRT consisted of 60 Gy intensity modulated radiotherapy with concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the other hand, only 22% of patients in the CACTUX trial received PD-1 inhibitor immunotherapy after progression and demonstrated a: median PFS of 2.2 months. 33 Comparatively, in our study, 19 of 33 patients who progressed (57.5%) received immunotherapy (nivolumab) and showed good response with an ORR of 26.3% and median PFS and OS of 6.5 months and 20.6 months, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, only 22% of patients in the CACTUX trial received PD-1 inhibitor immunotherapy after progression and demonstrated a: median PFS of 2.2 months. 33 Comparatively, in our study, 19 of 33 patients who progressed (57.5%) received immunotherapy (nivolumab) and showed good response with an ORR of 26.3% and median PFS and OS of 6.5 months and 20.6 months, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…The effects of carcinogen were also not mentioned in the Chinese and Korean population. The results of these studies are summarized in Table 6 ( Adkins et al, 2018 ; Bossi et al, 2017 ; De Mello et al., 2014 ; Friesland et al., 2018 ; Guigay et al, 2016 ; Guigay et al, 2012 ; Guigay et al, 2019 ; Guo et al., 2015 ; Tahara et al, 2016 ; Vermorken et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of cetuximab to platinum-based chemotherapy with fluorouracil (platinum-fluorouracil) improved the overall response rates, median progression-free survival (PFS), and overall survival (OS) compared with chemotherapy alone. Another combination of cetuximab with chemotherapy agents such as taxane also demonstrated substantial benefits ( Adkins et al, 2018 ; Friesland et al., 2018 ; Guigay et al, 2019 ). However, most of these clinical trials were conducted in Western countries with fewer patients with primary oral cavity cancer; data regarding the effect of carcinogens such as betel nuts on outcome are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fluorouracil to a taxane seeks to take advantage of the potential immunogenic and proapoptotic synergy between cetuximab and docetaxel or paclitaxel[ 12 , 13 ]. Cetuximab-, platinum-, and taxane-based schedules have been associated with promising survival results and cytoreductive properties in clinical studies[ 14 - 18 ]. TPExtreme was the first large, phase 3, randomized trial comparing the TPEx regimen (cetuximab, taxane, and platinum) with the EXTREME scheme in a first-line setting[ 19 ].…”
Section: Introductionmentioning
confidence: 99%